THE HOMELAND IS AS SACRED AS A SHRINE - Ahmadaliyev Muhammadali Gaybillojonovich; Abdumuttaliyev Sardorbek Ahadjonovich; Muminov Azizbek Tojalievich (Scholar Express Journal, 2022)
The motherland is the sacred land where a person is born. By the motherland we mean the motherland where our parents and descendants shed their umbilical cord blood. In order to feel the homeland deeply in the heart, it is necessary to know, respect, appreciate and strengthen the examples of patriotism of the people. These feelings, these beautiful high human qualities are a true example of patriotism for our free day. That is, the nation is the pillar of the Motherland
Keywords: Loyalty; love for the motherland; universal feeling; spiritual values